Contribution to the characterization of the seed endophyte microbiome of Argania spinosa across geographical locations in Central Morocco using metagenomic approaches - Sohaib, Hourfane; Fays, Morgan; Khatib, Abderrezzak; Rivière, John; El Aouad, Noureddine; Desoignies, Nicolas (Frontiers in Microbiology, 2024)
Microbial endophytes are microorganisms that live inside plants, some of them play important yet understudied roles in plant health, growth, and adaptation to environmental conditions. Their diversity within plants has traditionally been underestimated due to limitations of culture-dependent techniques. Metagenomic profiling provides a culture-independent approach to characterize entire microbial communities. The argan tree (Argania spinosa) is ecologically and economically important in Morocco, yet its seed endophyte microbiome remains unexplored. The aim of this study was to compare the bacterial and fungal endophyte communities associated with argan seeds collected from six sites across Morocco using Illumina MiSeq sequencing of the 16S rRNA gene and ITS regions, respectively. Bacterial DNA was extracted from surface-sterilized seeds and amplified using universal primers, while fungal DNA was isolated directly from seeds. Bioinformatic analysis of sequencing data identified taxonomic profiles at the phylum to genus levels. Results showed that bacterial communities were dominated by the genus Rhodoligotrophos, while fungal communities varied between Ascomycota and Basidiomycota dominance depending on site, with Penicillium being most abundant overall. Distinct site-specific profiles were observed, with Pseudomonas, Bacillus and Aspergillus present across multiple locations. Alpha-diversity indices revealed variation in endophyte richness between seed sources. In conclusion, this first exploration of the argan seed endophyte microbiome demonstrated environmental influence on community structure. While facing limitations due to small sample sizes and lack of ecological metadata, it provides a foundation for future mechanistic investigations into how specific endophyte-host interactions shape argan adaptation across Morocco's diverse landscapes.